Bibliometric Analysis of School Religious Activities in Developing Students' Morality in Indonesia - Ali Anhar Syi'bul Huda; Fahrudin Fahrudin (At-Tarbiyat, 2024)
This study aims to map, describe, and analyze scientific articles on school religious activities in fostering the morals of students in Indonesia. The research was conducted in December 2023 through a Google Scholar database search with the title of religious activities. Specifically, the maximum number of results was 500 articles as a sample, and the publication ranged from 2016 to 2023. Metadata retrieval using the Publish or Perish (PoP) application version 8.12. The PoP data was then analyzed descriptively based on the year of publication, publication source, researcher productivity, and journal rank. To get an accurate map of research development, PoP data is exported to the PoPCites file format, which will then be mapped simply using Excel and Result as RIS. Researchers map POPCites data, which are then entered into the previously created table, and RIS data is analyzed using the VOSViewer (VV) application version 1.6.20. The results showed that the publication of research regarding school religious activities from 2016-2023 experienced an exponential increase, and the largest source of publication through e-journals was 255 articles. The researchers who produced publications were four people, namely Aini Nur Azizah, Muhammad Hanief, Fita Mustafida, and Imam Syafi'i, with each publication of 2 articles. The VV visualization application shows that the research development map of school religious activities consists of 5 clusters. Cluster 1 has seven topics, cluster 2 has four topics, cluster 3 has three topics, cluster 4 has two topics, and Cluster 5 has one topic with the most research covering the topics of religious activities, activities, religion, and through religious activities.